2020
DOI: 10.1002/hed.26425
|View full text |Cite
|
Sign up to set email alerts
|

Keys to successful implementation of routine symptom monitoring in head and neck oncology with “Healthcare Monitor” and patients' perspectives of quality of care

Abstract: Background: Value-based health care is increasingly used to facilitate a systematic approach during follow-up of patients. We developed Healthcare Monitor (HM): a structure of electronic patient-reported outcome measures (ePROs) for the longitudinal follow-up of head and neck cancer (HNC) patients. This study shares key lessons from implementation and seeks to provide insight into how patients experience HM. Methods: We conducted a mixed-methods study using quantitative data from a nonrandomized retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 30 publications
(94 citation statements)
references
References 37 publications
1
93
0
Order By: Relevance
“…Only 22 of the 40 empirical studies evaluated the implemented VBHC components. Eighteen studies measured the effects primarily quantitatively [ 9 , 14 , 15 , 18 , 19 , 24 26 , 32 – 35 , 39 – 42 , 44 , 50 ] two qualitatively [ 8 , 29 ] and two studies combined quantitative research methods with a qualitative approach [ 17 , 36 ], using a mixed-methods design. The studies that measured the effects of implementing ‘measure outcomes and costs for every patient’ ( N = 4) reported a decrease in healthcare costs [ 32 ], as well as an increased number of patients that felt that the provider spent enough time with them [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only 22 of the 40 empirical studies evaluated the implemented VBHC components. Eighteen studies measured the effects primarily quantitatively [ 9 , 14 , 15 , 18 , 19 , 24 26 , 32 – 35 , 39 – 42 , 44 , 50 ] two qualitatively [ 8 , 29 ] and two studies combined quantitative research methods with a qualitative approach [ 17 , 36 ], using a mixed-methods design. The studies that measured the effects of implementing ‘measure outcomes and costs for every patient’ ( N = 4) reported a decrease in healthcare costs [ 32 ], as well as an increased number of patients that felt that the provider spent enough time with them [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…The qualitative analyses in the two mixed-methods studies found that dedicated resources, change of culture and improved knowledge and awareness about VBHC are crucial for implementation [ 36 ]. Furthermore, patients experienced better doctor-patient communication after VBHC implementation [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Information on survival is not a standalone concept and should be combined with information on QoL. Due to the implementation of our Healthcare Monitor 50 we are currently obtaining QoL data. Future research will focus on modeling QoL together with survival.…”
Section: Discussionmentioning
confidence: 99%
“…Hopefully, this model will take away some reluctance to discuss the prognosis in the palliative phase, and give rise to more realistic prognostic discussions. Due to the implementation of our Healthcare Monitor [48] we are routinely collecting data on the QoL and functioning in the palliative phase, using the EORTC QLQ-C15-PAL [20]. These data can be used in future prognostic research to model QoL.…”
Section: Clinical Implications and Future Researchmentioning
confidence: 99%